Practice of walking, moderate and vigorous physical activity and associated factors in first year undergraduate students - Gaia Salvador Claumann; Érico Felden Pereira; Andreia Pelegrini (Desafio Singular, 2014)
The changes that occur with the beginning of university life may interfere with the practice of physical activities by students. The aim was to investigate the association between the practice of walking, moderate and vigorous physical activities with sociodemographic factors and weight status in freshman students in the first semester of the first year of a public university in Florianopolis/SC. This study assessed198 students (86 men and 112 women). The practice of physical activities was collected with the International Physical Activity Questionnaire - IPAQ, short version. Students of human and educational sciences reported higher amounts of moderate physical activity when compared to health and exact science counterparts (p< 0.05). It was verified that male students, from higher economic status, from the health sciences, and full-time students showed higher time of practice of vigorous physical activity (p< 0.05). Significant associations were also observed between study period and walking, and between gender, scientific field and vigorous physical activity. It was concluded that the variables associated with the practice of physical activity differ according to the type and intensity of physical activity.